THE USE OF GUIDED READING STRATEGIY (GRS) TO INCREASE READING COMPREHENSION AT THE ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL ETHIKA OF PALEMBANG - Rani Puspitasari; Farnia Sari (Universitas Tridinanti Palembang, 2020)
This study was conducted to find out whether or not there was significant difference in reading comprehension between those students who were taught by using guided reading and those students who were not at the eleventh grade students of Ethika Senior High School of Palembang. The sample of the study was 68 students of the eleventh grade students of SMA Ethika Palembang n the academic year of 2015/2016 that were taken by using intact sampling technique. Thirty four students were in the exerimental group and thirty four students were in the control group. Experimental research by using quasi-experimental was used. The used instrument was in the form of 30 items of multiple choice questions. The results of the test were analyzed by using t-test (paired sample t-test and independent t-test). The result of paired sample t-test from experimental group was 7.165, it was more than t-table 2.0322 with df was 34 students. Based on independent sample t-test analysis, it was found that t-obtained was 2.556 at the significant level p<0.05 (5%). The critical value of test was 1.9955 with df was 68 students, so that 2.556 >1.995. It means that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It could be concluded that there was significant difference in students’ reading comprehension between those students who were taught by using guided reading and those who were not.Keywords: Improving, Reading Comprehension, and Guided Reading